How Forest Therapy Fosters Inner Development - The Missing Piece in Sustainability - Amanda Yik (The Journal of the International Association of Adventure and Nature Based Therapies, 2026)
This article explores a potential thread that may connect how spending time in nature can help create a better, more sustainable future for all, referencing the practice of Relational Forest Therapy and the Inner Development Goals (IDG) Framework. More people have begun to appreciate Forest Therapy or Forest Bathing as a holistic wellbeing practice that offers far beyond physical health benefits. It can support us to live purposeful, sustainable, and productive lives by cultivating a shift in human values and developing an inner life that fosters positive change.